Natural products chemistry: The emerging trends and prospective goals - Riaz A. Khan (Elsevier, 2018)
The role and contributions of natural products chemistry in advancements of the physical and biological sciences, its interdisciplinary domains, and emerging of new avenues by providing novel applications, constructive inputs, thrust, comprehensive understanding, broad perspective, and a new vision for future is outlined. The developmental prospects in bio-medical, health, nutrition, and other interrelated sciences along with some of the emerging trends in the subject area are also discussed as part of the current review of the basic and core developments, innovation in techniques, advances in methodology, and possible applications with their effects on the sciences in general and natural products chemistry in particular. The overview of the progress and ongoing developments in broader areas of the natural products chemistry discipline, its role and concurrent economic and scientific implications, contemporary objectives, future prospects as well as impending goals are also outlined. A look at the natural products chemistry in providing scientific progress in various disciplines is deliberated upon. Keywords: Emerging trends, Natural products chemistry, Perspective, Prospects